FOODEGA: Mobile Food Management Application - Mohd Am Jaid, Arfa Farheen (IRC, 2020)
Food waste is one of the major problems faced by humanity today. However so, many do not consider it as a real issue as they have the means and access to food on the daily and do not fully grasp the weight of the issue. In this research, a mobile food management application across all (Android, iOS and Windows) mobile platformsis proposed as a solution. The goal is to promote a more mindful and efficient approach to overcoming food wastage within households.